APLIKASI SISTEM INFERENSI FUZZY METODE TSUKAMOTO DALAM PENILAIAN MUTU BENIH PADI - Diasta Risi Esa Annisa; Mutia Nur Estri (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2015)
In this paper, we use the Fuzzy inference system of Tsukamoto method to determine the rice seeds quality. The input variables are production average, the age of plant, and fallen seeds, and the output variable is rice seed quality. The output is determined through 4 steps i.e. fuzzification, determine fuzzy rules, and defuzzification. The results show that the best quality of rice seed is IR 64 and the worst is Lusi.